2012
DOI: 10.1111/j.1095-8649.2012.03384.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of stock components using morphological markers

Abstract: This study investigated the development of a quantitative method for distinguishing stock components of Icelandic cod Gadus morhua based on visual examination of morphology. The stock is known to be structured into genetically distinct geographic components (north and south of Iceland) and behavioural types that spawn sympatrically. Differences in morphology were tested between locations, genotypes (a proxy for behaviour) and sexes. Results show morphological markers on the head, fins and body of G. morhua tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…EBC have narrower otoliths [ 23 , 29 ] and a more streamlined body shape [ 62 , 63 ], which may be attributed to the differences in the foraging and movement behaviour of the cod stocks. Other studies showed similar adaptations on otolith and body morphology in migratory cod [ 22 , 64 , 65 ], suggesting that a more streamlined otolith and body shape is advantageous for foraging in deeper waters and more active swimming behaviour.…”
Section: Discussionmentioning
confidence: 60%
“…EBC have narrower otoliths [ 23 , 29 ] and a more streamlined body shape [ 62 , 63 ], which may be attributed to the differences in the foraging and movement behaviour of the cod stocks. Other studies showed similar adaptations on otolith and body morphology in migratory cod [ 22 , 64 , 65 ], suggesting that a more streamlined otolith and body shape is advantageous for foraging in deeper waters and more active swimming behaviour.…”
Section: Discussionmentioning
confidence: 60%
“…In response to the increasing demands for identifying stock units, development of pertinent methods has steadily progressed (Cadrin et al , 2014a. Traditional methods, such as the use of life history parameters, morphometrics, or parasites as natural markers, are still part of the toolbox (Baldwin et al 2012;McAdam et al 2012;Zischke et al 2013;Cadrin et al 2014a). New technologies, such as otolith microchemistry, single-nucleotide polymorphisms, or electronic tags, have greatly expanded the toolbox (Hodgins- Davis et al 2007;Rooker et al 2007;Walther et al 2008;Cadrin et al 2014a).…”
mentioning
confidence: 99%
“…Morphological differences have been reported in many marine pelagic species, especially in clupeids (Thomas et al., ). In Atlantic cod Gadus morhua , morphological differences were associated with behavioural and ecological differentiation (McAdam et al., ). The two behavioural types, coastal and frontal, were associated with distinct morphological characteristics such as gape of mouth, eye position and spaces between fins and depth of body.…”
Section: Discussionmentioning
confidence: 99%